PEMIKIRAN EKONOMI ILMUWAN MUSLIM KONTEMPORER MADZHAB IQTISHODUNA - Mohammad Robbi Maulana; Rofiyana; Firda Nadyarahma; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study is to explain the Iqtishoduna school of economic philosophy of modern Muslim thinkers. Therefore, every hypothesis generated by conventional economics is rejected and ignored. Instead, the aim of this school is to create unique theories taken directly from the Quran and Sunnah. This school was founded by Baqir As-Sadr, who wrote the book Iqtishaduna (Our Economy). This school argues that economics and Islam cannot be united. Economics is economics, and Islam is Islam. Problems arise from injustice and unfair distribution. The primary source for economic theory should be the Qur'an. The two can never be united because their mentalities are very different. One opposes Islam, and the other supports it. According to Sadr, one cannot fully analyze the Islamic economic system without first studying and understanding Islamic philosophy. Baqr Ash-Sadr's economic theory states that religion is very important in the Islamic economic system because it recognizes that humans have social and personal interests that may conflict and produce problems. Sadr thinks that these problems can be solved through faith. The Pahlavi Shah regime severely oppressed Iran during Ali Shariati's lifetime. This affected the socio-political climate of the time.